Enredos: Eva Fàbregas - Lafarge, Daisy; Martínez, Chus 1972-; Rodríguez Muñoz, Bárbara (Fundación Botín, 2023)
Published on the occasion of the first chapter of "Enredos"—Centro Botín’s new exhibition programme engaging artists who received a Fundación Botín grant in the past to "become entangled" with the Foundation’s collection, building, and audiences—this is the debut publication of the Spanish artist Eva Fàbregas. In her works Fàbregas explores tactility, physical intimacy, and various forms of somatic experimentation, reinforcing the need to feel the world around us through perception—soft plastics, nets, lycras, technological devices: all have one thing in common, they are malleable. Many titles of her works allude to natural processes, again inviting us to relate to art viscerally
Exposición y catálogo. - Genaue Ausstellungsdaten ermittelt: 20 May - 15 October 2023
Keywords: Fàbregas, Eva -- 1988-; Ausstellungskatalog -- Centro Botín -- 20.05.2023-15.10.2023 -- Santander